Technical and Environmental Performance Evaluation of Fuel Switching from Coal to Biomass Wood Chip in Circulating Fluidized Bed Boiler - Habibi, Muhamad; Wicaksono, Sigit Tri (Spektra: Jurnal Fisika dan Aplikasinya, 2025)
Presidential Regulation No. 112 of 2022 regulates the preparation of a road map to accelerate the termination of operating time for steam power plants (PLTU). Biomass’s potential to reduce emissions compared to coal explains why PLTU was chosen for this study. The operation of a PLTU requires the replacement of non-renewable electricity fuel sources with renewable ones. PLTUs are dominated by the use of coal. In accordance with presidential regulations, this research carried out fuel switching from coal to biomass. This research was conducted at PLTU Bolok, Kupang Regency. PLTU Bolok has a capacity of 2×16.5 MW. Fuel switching from coal to wood chip biomass in a Circulating Fluidized Bed (CFB) type boiler was carried out directly (direct co-firing), with five combustion treatments, namely, 100% coal and 0% biomass, 75% coal and 25% biomass, 50% coal and 50% biomass, 25% coal and 75% biomass and 0% coal and 100% biomass. The results of this research show that the performance of the biomass fuel switching caused the PLTU unit to experience a derating of 2 mW/hour. The results of other parameter analysis are FEGT 845.33 °C, furnace pressure -35 Pa and furnace temperature 947.04 °C. NOx emissions were reduced by 11.3 mg/Nm3, SO2 by 45.8  mg/Nm3 and CO2 12.5 mg/Nm3. The environmental benefit is the reduction emissions.